Simple Access to 3-(Hetero)arylated Derivatives of 2-Furoic Acid via Ru(II)-Catalyzed C3-H Arylation of 2-Furoylimidazole - Shepelenko, Konstantin E.; Gnatiuk, Irina G.; Lavrentev, Igor V.; Minyaev, Mikhail E.; Chernyshev, Victor M.; Ananikov, Valentine P. (Synthesis, 2024)
A new approach for the preparation of a variety of 3-arylated 2-furoic acid derivatives has been developed. The approach involves selective Ru-catalyzed C3-H arylation of the furan moiety of readily available 2-furoyl-1-methylimidazole (using imidazole as a removable N-donor directing group), subsequent N-methylation, and nucleophilic substitution of the imidazole moiety with N, O, S, and C nucleophiles.
Keywords: 2-furoic acid; ruthenium; C–H activation; arylation; directing groups; nucleophilic substitution